Spindle Cell Carcinoma Presenting as a Lung Cancer: A Seldom-Seen Case - Ali Goudarzi; Leila Ostovar (Case Reports in Clinical Practice)
Pulmonary spindle cell carcinoma (PSCC) is a rare and highly aggressive form of nonsmall cell lung cancer with sarcomatoid differentiation. It poses significant diagnostic challenges due to its histological resemblance to other malignancies, including inflammatory myofibroblastic tumors. This case report details the clinical presentation, histopathological findings, and treatment of a patient with PSCC, to further elucidate the clinical features, diagnosis, and management of this rare tumor.